Student Satisfaction with Private Tertiary Education Provision in South Africa in the Times of #FeesMustFall - Jingura, Valentine; McKay, Tracey; Simpson, Zach (International Journal of African Higher Education, 2022)
Against the backdrop of a growing population and increased demand for tertiary education, South Africa’s private higher education sector has grown considerably since 1994. However, it has long been beset by perceptions of poor quality. This study surveyed private university students to gauge their satisfaction with their institutions. It also explored whether, as posited by some scholars, the disruptions caused by the #FeesMustFall movement across South African public universities may result in greater private tertiary education enrolment. The students who participated in the online survey expressed moderate satisfaction with their universities. Their biggest concern was the high cost of private tuition. Moreover, they were sympathetic to the #FeesMustFall movement, expressing a willingness to enroll in public education in the future. Nonetheless, concerns regarding safety and security in public universities loomed large, whereas they were confident that their private institutions fully met their safety and security needs. Key words: Private higher education; South Africa; student satisfaction; voice exit loyalty; higher education studies